BLENDED LEARNING IN ESL/EFL CLASS - Menggo, Sebastianus; Darong, Hieronimus Canggung (LLT Journal: A Journal on Language and Language Teaching, 2022)
Blended learning requires digital technology transformation for lecturers and students, up-to-date teaching methods, flexible learning processes, the effectiveness of time, space, budget, learning motivation, learning autonomy, all of which contribute to improving student learning achievement. However, current empirical research results do not support the claim that blended learning improves students' English proficiency and learning autonomy. Evidence shows that the blended learning has an effect on students' English competence, learning autonomy, motivation, and ICT literacy. For this article, the effect of blended learning in ESL/EFL was investigated and defined. This study is a quantitative explanatory research type with a pre-test and post-test design. The research participants were 198 students from the Department of Primary School Teacher Education, Universitas Katolik Indonesia Santu Paulus Ruteng. Seventy-four participants were chosen as samples using a random sampling method. Data was taken by test and non-test, and data was then analysed by a software program called SPSS 22.0. Twelve blended learning sessions, including six sessions in face-to-face settings and six sessions, are done virtually through the Zoom application. The results show that blended learning strengthens English student competence (the mean score on the post-test = 82.57), learning autonomy (88.57%), learning motivation (80%), and ICT literacy (71.43%).